Hyperacusis and disorders of sound intolerance : clinical and research perspectives - Fagelson, Marc; Baguley, David (David M.) (Plural Publishing, Incorporated, 2018)
This is a professional resource for audiology practitioners involved in the clinical management of patients who have sound tolerance concerns. The text covers emerging assessment and intervention strategies associated with hyperacusis, disorders of pitch perception, and other unusual processing deficits of the auditory system. In order to illustrate the patients' perspectives and experiences with disorders of auditory processing, cases are included throughout.